Organ Donation Decision in Families With Brain-Dead Patients: An Evolutionary Concept Analysis. Issue 2 (March 2022) - Rafii, Forough; Rahimi, Sara
Abstract : Background and Aim: Organ donation decision is a complicated process for bereaved families; however, its attributes and associated factors are not clear. Accordingly, the purpose of this study was to analyze the concept of organ donation decision in families with brain-dead patients. Methods: Concept analysis was performed using Rodgers' evolutionary method. For this purpose, PubMed, OVID, Scopus, and ProQuest databases were searched in English from 1985 to 2019. In total, 54 articles were analyzed using the thematic analysis to identify the attributes, antecedents, and consequences of the concept. The validity of the data was provided by examining the analysis process by 2 independent researchers. Findings/Conclusions: Organ donation decision in these families is a complicated and conflicting process of vicarious decision-making that begins with an organ donation request: a difficult, painful, and critical experience that requires extensive interpersonal interactions and is ultimately influenced by various factors, leading to the acceptance or refusal. The antecedents include deceased-related factors, family-related factors, the quality of organ donation request, and the quality of health care professionals' interactions. The consequences include the positive outcomes (grief solace, gift of life, and promoting human values) and negative outcomes (ambiguity, doubt and regret, and psychological inconsistency). The results of this concept analysis led to a better understanding of the complexity of an organ donation decision in these families. In this way, in addition to knowledge development, it assists the health care staff to support families in making the organ donation decision. Implications for Case Management Practice: Although case managers rarely participate in organ donation, they definitely need to understand the concepts related to organ donation decision while advocating for the patients or families. The results of this concept analysis can broaden the case managers' and other health care professionals' knowledge about families' organ donation decision and help them take more effective interventions for management of this process. Case managers and the health care team can use the information of this article for informing families about brain death, negotiating with families for organ donation, preparing information, and caring and facilitating the families in making the clear and unconflicted decision.